Callus induction and plant regeneration on optimization of the culture conditions in Jow Haw rice (Oryza sativa L.) - Poraha, R.; Poeaim, A.; Pongjaroenkit, S.; Pongthongkam, P. (International Journal of Agricultural Technology, 2016)
The objective of this study was to develop an efficient protocol for optimum callus induction and regeneration of Jow Haw (Oryza sativa L.). MS (Murashige and Skoog) and NB (Nitch and Nitch) media supplemented with 0.5 mg/l NAA (α-Naphthaleneacetic acid) and 0.5, 1, 2, 3 and 5 mg/l 2,4-D (2,4-Dichlorophenoxyacetic acid) in different concentrations were used for callus induction. The callus induction frequencies were 90-100% on NB medium containing 3 mg/l 2,4-D for 4 weeks. The maximum mean size of callus was 181.76 mm3 and mean fresh weight of callus was0.2552 g. For plant regeneration the callus were cultured on MS and NB media containing with 0.5 mg/l NAA and different concentrations of 1, 2 and 3 mg/l BAP (6-Benzylaminopurine). The highest regeneration frequency (100%) was grown on MS medium containing with 2 mg/l BAP in 5.2 g/l phytagel. Complete plantlets were regenerated in 6 weeks. When the plantlets regeneration were be strong. Then transferred to the sterile soil into pots.